2016
DOI: 10.1111/phpp.12236
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term chemical pretreatment cannot replace curettage in photodynamic therapy

Abstract: Curettage significantly enhances PpIX fluorescence from 1 to 5 h and is superior to short-term chemical pretreatment. Our results support curettage as standard pretreatment in PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The amount of ALA-induced PpIX was at least threefold higher at any measured time point [53]. Two additional studies could reproduce the increased PpIX formation attributed to BF-200 ALA compared with MAL in healthy volunteers' skin, focusing on either different age groups or pretreatments [66,67].…”
Section: Enhancing Pdt With Nanoemulsion Technologymentioning
confidence: 83%
See 1 more Smart Citation
“…The amount of ALA-induced PpIX was at least threefold higher at any measured time point [53]. Two additional studies could reproduce the increased PpIX formation attributed to BF-200 ALA compared with MAL in healthy volunteers' skin, focusing on either different age groups or pretreatments [66,67].…”
Section: Enhancing Pdt With Nanoemulsion Technologymentioning
confidence: 83%
“…Interestingly, the nanoemulsion BF-200 seems to enhance penetration as well as epidermal PpIX formation [53,64,66,67]. In a porcine skin model in vitro, BF-200 ALA containing 7.8% ALA was shown to be superior compared with a 20% MAL formulation, containing 16% free MAL, in terms of penetration depth and PpIX formation in the deeper epidermal layers [64].…”
Section: Enhancing Pdt With Nanoemulsion Technologymentioning
confidence: 99%
“…In a recent study, we monitored PpIX fluorescence in 30 healthy individuals during a 24-h application of MAL and investigated the effect of pretreatment with curettage. 7 The results showed that PpIX accumulation after 21 h was > 300% higher than after the standard application time of 3 h. Furthermore, curettage in itself increased PpIX accumulation significantly. 7 In the present study, we used both methods to enhance PpIX accumulation and we investigated whether increased PpIX accumulation could improve PDT efficacy when treating AKs on the dorsal side of the hands.…”
Section: What Is the Translational Message?mentioning
confidence: 93%
“…It is possible to increase PpIX accumulation by extending the application time of MAL and/or pretreating the skin before MAL application. In a recent study, we monitored PpIX fluorescence in 30 healthy individuals during a 24‐h application of MAL and investigated the effect of pretreatment with curettage . The results showed that PpIX accumulation after 21 h was > 300% higher than after the standard application time of 3 h. Furthermore, curettage in itself increased PpIX accumulation significantly …”
mentioning
confidence: 99%
“…Another study from the same group monitoring PpIX fluorescence in healthy individuals during 24‐h application of MAL demonstrated a 300% higher PpIX accumulation than after a 3‐h application, and that furthermore, curettage also increased PpIX accumulation significantly . The inferior efficacy rates obtained with PDT on acral parts of the upper extremities, which often have rather thick actinic keratosis (AK) lesions, have been believed to be caused by insufficient PpIX production and accumulation.…”
mentioning
confidence: 99%